(untitled) (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2024)
Background: The age of adolescents is the most vulnerable age to experience reproductive health problems. Basic Health Research Results (2013) showed in DIY the prevalence of adolescents with malnutrition status was 2.4%, underweight nutrition at 4.9%, and obesity by 4.2%. The health status of today’s adolescents will determine the picture of the health status of the adult population in the following decade, therefore adolescent health occupies an important position on a global scale. Objective: To find out the relationship between the knowledge of young women about reproductive health and nutritional status in SMA Negeri 1 Srandakan. Research Methods: Quantitative research, with analytic survey design, cross-sectional approach, population 148 and samples taken 66 using stratified random sampling techniques, data collection tools using questionnaires, univariate analysis with frequency distribution and bivariate analysis using Kendal-tau. Results: Knowledge of young women about reproductive health with a good category (53.1%) with normal nutritional status. Knowledge of good categories (34.7%) with underweight nutritional status and good level of adolescent knowledge (12.2%) with overweight nutritional status. There is no significant relationship between the level of knowledge of reproductive health with adolescent nutritional status p-value (0.313)> significant level (0.05). Conclusion: There is no relationship between the knowledge of young women about reproductive health and nutritional status in SMA Negeri 1 Srandakan Keyword: Adolescents, knowledge of reproductive health, nutritional status